Continental Evolution: The Geology of Morocco - S. Bhattacharji, H. J. Neugebauer, J. Reitner, K. Stüwe, G. M. Friedman, A. Seilacher, André Michard, Omar Saddiqi, Ahmed Chalouan, Dominique Frizon de Lamotte. (Springer, 2017)
438p.